A Practical Guide to Building Professional Competencies in School Psychology - Lionetti, Timothy M.; Snyder, Edward P.; Christner, Ray W.; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2011)
Designed as a research-based yet matter-of-fact guide for beginning and future scientist-practitioners, A Practical Guide to Building Professional Competencies in School Psychology skillfully augments the reader$1 (Bs training, supervision, and experience by providing a framework for honing essential skills in the field. This reader-friendly, evidence-based text encourages the continuing development of expertise in communication and collaborative skills, diversity awareness, technical knowledge, and other domains critical to building and maintaining an ethical, meaningful practice. Each chapter in this must-have volume examines a core area of expertise in depth, and provides checklists (linked to competencies set out in NASP$1 (Bs Blueprint III) and the Development and Enhancement of Competencies Assessment Form are included to enable readers to gain a more complete understanding of their professional strengths and needs. The skill sets covered include: Developing cross-cultural competencies. Evaluating students with emotional and behavioral problems. Assessing student skills using a variety of approaches. Preventing and intervening in crisis situations. Consulting with families, colleagues, and the community. Facilitating mental health services in the school setting. A Practical Guide to Building Professional Competencies in School Psychology provides an invaluable set of professional development tools for new practitioners and graduate students in school psychology.s
Acknowledgments -- About the Editors -- List of Contributors -- Developing and Enhancing Competencies in the Practice of School Psychology -- Applying Law and Ethics in Professional Practice -- Building Competency in Cross-Cultural School Psychology -- Managing Your Professional Practice as a School Psychologist -- Consulting with Families, Schools, and Communities -- Assessing Student Skills Using a Nontraditional Approach -- Assessing Student Skills Using Process-Oriented Approaches -- Evaluating Students with Emotional and Behavioral Concerns -- Beyond Unproven Trends: Critically Evaluating School-wide Programs -- Advocating for Effective Instruction: School Psychologists as an Instructional Leader -- Facilitating Mental Health Services in Schools: Universal, Selected, and Targeted Interventions -- Preventing and Intervening in Crisis Situations -- Developing Competent Written and Oral Communication -- Using Advancing Technologies in the Practice of School Psychology -- Making A Career of School Psychology -- Monitoring Professional Competence in School Psychology.
Keywords: Philosophy (General).; Developmental psychology; Psychology; Child and School Psychology; Education (general).